Assessing Factors Impacting College Students’ Attitudes and Behavioral Intentions Toward Augmented Reality Technologies in Yibin, China - Chen , Jing; Gu, Qizhen (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study assessed the factors influencing the attitudes and behavioral intentions of college students in Yibin, China, regarding the use of augmented reality (AR) technology. The research focused on students aged 18 and above who showed interest in AR technology. This study leverages three significant theoretical models（TAM, UTAUT, IDT）to enhance and refine the conceptual framework. The conceptual framework included interactivity, innovation, perceived usefulness, sense of presence, perceived ease of use, attitude, and behavioral intention. A total of 450 students from four different majors participated in the survey. The data collection process was carried out in three phases: purposive sampling, stratified random sampling, and convenience sampling. To ensure the quality of the data, experts conducted an Item-Objective Congruence (IOC) assessment of the survey items prior to data collection, followed by a pilot test with 50 participants. Through confirmatory factor analysis (CFA), the factor structure’s appropriateness and the model’s test were verified, demonstrating a satisfactory fit, with the following model fit indices: CMIN/dF = 2.385, GFI = 0.874, AGFI = 0.847, CFI = 0.949, TLI = 0.942, and RMSEA = 0.056. These indices confirm the reliability and validity of our constructs. Notably, perceived usefulness was identified as the most influential factor on attitude, which in turn significantly impacts behavioral intention. As technology continues to evolve, augmented reality (AR) is demonstrating extensive potential across various domains, including education, business, and entertainment. Given their role as early adopters of new technologies, college students are instrumental in driving the adoption and practical application of AR technology.